2021
DOI: 10.1108/jpbafm-11-2019-0168
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic tone of management discussion and analysis disclosures and the municipal debt market

Abstract: PurposeAs the management discussion and analysis (MD&A) section contains discretionary narrative disclosures regarding a government's yearly financial changes and status, the authors investigate several municipal debt market consequences of linguistic tone within these disclosures.Design/methodology/approachThe authors textually analyze municipal MD&As with Linguistic Inquiry and Word Count (LIWC) software and develop narrative tone measures based on existing financial-specific dictionaries. Using a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…A few studies document that linguistic tone serves as an explanation for the activities in both the equity market and the bond market (D'Augusta & DeAngelis, 2020b; Feldman et al, 2010; Huang, Teoh, & Zhang, 2014; Rich et al, 2021). However, the CDS market is a preferred place for investors to gather useful information relative to the stock market or the bond market for two reasons.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…A few studies document that linguistic tone serves as an explanation for the activities in both the equity market and the bond market (D'Augusta & DeAngelis, 2020b; Feldman et al, 2010; Huang, Teoh, & Zhang, 2014; Rich et al, 2021). However, the CDS market is a preferred place for investors to gather useful information relative to the stock market or the bond market for two reasons.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This suggests sentiment can help to predict intraorganizational outcomes like audit findings. More recent work offers initial evidence that among local governments, negative sentiment in the MD&A disclosures can increase future debt issuance costs (Rich, Roberts, and Zhang 2021). Future work should continue to explore these capital markets effects, and explore whether the same is true of budget expansions or cuts, revenue forecast accuracy, revenue volatility or stability, and other key financial outcomes.…”
Section: Financial Sentiment In Social Media-the Implicationsmentioning
confidence: 99%
“…Li (2010) found that future earnings and liquidity are better when the Management Discussion and Analysis (MD&A) section of the financial statements is more positive. Rich et al (2021) studied the relationship between the tone in the MD&A section of the financial statements and the municipal debt market and found that a more negative tone is associated with higher future debt costs and greater future disagreements among bond rating agencies.…”
Section: Tonementioning
confidence: 99%